On the structure of the algebra of derivations of cyclic Leibniz algebras - Kurdachenko, L.A.; Semko, M.M.; Yashchuk, V.S. (Algebra and Discrete Mathematics, 2021)
We describe the algebra of derivation of finitedimensional cyclic Leibniz algebra.